Wpływ edukacji zdrowotnej na zachowania zdrowotne dzieci w wieku przedszkolnym w opinii rodziców = Health education influence on health behaviors of preschool children in the opinion of their parents - Dominik Olejniczak; Wioleta Święcka; Joanna Skonieczna; Grażyna Dykowska (Kazimierz Wielki University, 2015)
Olejniczak Dominik, Święcka Wioleta, Skonieczna Joanna, Dykowska Grażyna. Wpływ edukacji zdrowotnej na zachowania zdrowotne dzieci w wieku przedszkolnym w opinii rodziców = Health education influence on health behaviors of preschool children in the opinion of their parents. Journal of Education, Health and Sport. 2015;5(9):261-272. ISSN 2391-8306. DOI10.5281/zenodo.30539 http://dx.doi.org/10.5281/zenodo.30539 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%289%29%3A261-272 https://pbn.nauka.gov.pl/works/620092 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011-2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.08.2015. Revised 05.09.2015. Accepted: 06.09.2015.   Wpływ edukacji zdrowotnej na zachowania zdrowotne dzieci w wieku przedszkolnym w opinii rodziców Health education influence on health behaviors of preschool children in the opinion of their parents   Olejniczak Dominik, Święcka Wioleta, Skonieczna Joanna, Dykowska Grażyna   Zakład Zdrowia Publicznego, Warszawski Uniwersytet Medyczny Public Health Department, Medical University of Warsaw   Słowa kluczowe: higiena, promocja zdrowia, przedszkolaki. Key words: health promotion, hygiene, preschool.   Streszczenie   Wprowadzenie: Wiek przedszkolny to najlepszy okres rozwojowy do kształtowania nawyków, postaw i umiejętności życiowych. Rodzina i przedszkole to środowiska, w których występuje edukacja zdrowotna dziecka. Od rodziny oczekuje się stworzenia warunków zapewniających bezpieczeństwo i zaspokojenie zdrowotnych potrzeb dziecka, a także organizacji życia zgodnego z zasadami higieny somatycznej i psychicznej. Dziecko przebywa w przedszkolu wiele godzin, zdobywa podstawowe informacje i umiejętności dbania o zdrowie i bezpieczeństwo. Cel pracy: Ocena wpływu edukacji zdrowotnej na zachowania zdrowotne dzieci w wieku przedszkolnym z perspektywy rodziców. Materiał i metody: Badanie zostało przeprowadzone metodą sondażu diagnostycznego. Wykorzystanym narzędziem był autorski kwestionariusz. Grupę badaną stanowiło 105 rodziców w 1. etapie badania oraz 127 rodziców w 2. etapie badania. Wyniki: Większość ankietowanych (76%) jest zdania, że wczesna edukacja zdrowotna ma bardzo duże znaczenie dla rozwoju i stanu zdrowia dzieci. Około 77% badanych rodziców jest zdania, że dzieci wykorzystują wiedzę zdobytą w przedszkolu w życiu codziennym. Połowa badanych (52%) jest zdania, że zachowania zdrowotne dzieci znacznie się poprawiły po zajęciach z edukacji zdrowotnej. Wnioski: Rodzice doceniają rolę wczesnej edukacji zdrowotnej w rozwoju i zdrowiu dzieci. Edukacja zdrowotna w przedszkolu przyczynia się do wzrostu zainteresowania zdrowiem wśród dzieci. Środowisko rodzinne może mieć pozytywny wpływ na zachowania prozdrowotne dzieci. Część rodzin nie zapewnia dzieciom właściwych warunków do wychowania zdrowotnego, dlatego należy rozważyć implementację działań edukacyjnych skierowanych do osób planujących bądź posiadających dzieci. Należy dążyć do zwiększenia roli osób wykonujących zawody medyczne w promocji zdrowia.   Abstract   Introduction: Preschool is the best period to acquire habits, attitudes and life skills. Family and kindergarden are environments where health education is performed. The family is responsible for creating conditions to ensure safety and meet the health needs of the child and for the organization of life compatible with the rules of somatic and mental health. The child spends many hours in preschool gaining basic information and skills about taking care of health and safety. Aim: The evaluation of health education influence on health behaviors of preschool children in the opinion of their parents. Material and Methods: The study was conducted using a diagnostic survey and a questionnaire designed by the author. The study included 105 parent in first phase and 127 parents in second phase. Results: The vast majority of respondents (76%) believe that early health education is very important for the child development and health. Approximately 77% of parents believes that children use the knowledge gained in preschool in everyday life. Half of parents (52%) believe that health behavior of their children significantly improved after health education classes. Conclusions: Parents appreciate the role of early childhood care in the development and health of children. Health education conducted in preschool contributes to increased interest in health among children. The family environment can have a positive impact on children's health behaviors. Some families do not provide children with appropriate conditions for health education. Implementation of educational actions directed to people planning or have children should be considered. The role of health professionals in health promotion should be increased.